PERALIHAN HAK ATAS TANAH MENGGUNAKAN KUASA JUAL OLEH PPAT BERDASARKAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 2016 ATAS PERUBAHAN PERATURAN PEMERINTAH NOMOR 37 TAHUN 1998 TENTANG PERATURAN JABATAN PEJABAT PEMBUAT AKTA TANAH. (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 3017 K/PDT/2019 JO PUTUSAN MAJELIS PEMERIKSA PUSAT NOTARIS NOMOR 08/B/MPPN/IX/2018) - Mutiara Indah Parawansa; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
The author discussed the PPAT's act of diverting the right to land owned by the seller using the Deed of Sale Power then there was a problem of the legality of the transfer of land rights by using the selling power by PPAT based on Government Regulation No. 24 of 2016 on Changes to Government Regulation No. 37 of 1998 concerning the Regulation of the Office of Land Deed Making Officers. (Case Study of Supreme Court Decision No. 3017 K/PDT/2019 Jo Verdict of The Notary Central Examiner No. 08/B/MPPN/IX/2018) and PPAT liability by transitioning land rights using the power of sale. (Case Study of Supreme Court Decision No. 3017 K/PDT/2019 Jo Verdict of The Notary Central Examiner No. 08/B/MPPN/IX/2018). The study uses normative juridical research. The results of the study obtained that the transfer of land rights using the Selling Power, The Binding Agreement for Sale and Emptying of Property Certificate Objects only has the power of the deed under the hand so that it can be requested.